SP7.1.5 Common General Surgical Never Events: Analysis of NHS England Never Events Data. (28th October 2021) - Omar, Islam; Singhal, Rishi; Wilson, Michael; Parmar, Chetan; Khan, Omar; Mahawar, Kamal
Abstract: Background: There is little available data on common general surgical Never Events (NE). Lack of this information may have affected our attempts to reduce the incidence of these potentially serious clinical incidents. The purpose of this study was to identify common general surgical NE from the data held by the NHS England. Methods: We analysed NHS England NE data from April 2012 to February 2020 to identify common general surgical NE. Results: There was a total of 797 general surgical NE identified under three main categories of Wrong-Site Surgery (n = 427;53.58%), Retained Items Post-Procedure (n = 355; 44.54%), and Wrong Implant/ Prosthesis and (n = 15; 1.88%). We identified a total of 56 common general surgical themes - 25 each in the Wrong-Site Surgery and Retained Foreign Body category and 6 in wrong implants. Wrong skin condition surgery was the commonest wrong-site surgery (n = 117; 27.4%). There were 18 wrong side chest drains (4.2%) and 18 (4.2%) wrong side angioplasty/angiogram. There were 7 (1.6%) instances of confusion in pilonidal/perianal/perineal surgeries and 6 (1.4%) instances of biopsy of cervix rather than colon or rectum. Retained surgical swabs were the most common retained items (n = 165;46.5%). There were 28 (7.9%) laparoscopic retrieval bags with or without the specimen, 26 (7.3%) chest drain guidewires, 26 (7.3%) surgical needles; and 9 (2.5%) surgical drains. Wrong stents were most common (n = 9;60%) wrong implant followed by wrong breast implants (n = 2;13.3%). Conclusion: This study found 56 common general surgical NE. Increased awareness of these common themes of NE may help reduce their incidence.